Geographical variation in certification rates of blindness and sight impairment in England, 2008–2009. Issue 6 (19th November 2012) - Malik, Aeesha N J; Bunce, Catey; Wormald, Richard; Suleman, Mehrunisha; Stratton, Irene; Gray, J A Muir
Abstract : Objectives: To examine and interpret the variation in the incidence of blindness and sight impairment in England by PCT, as reported by the Certificate of Vision Impairment (CVI). Design: Analysis of national certification data. Setting: All Primary Care Trusts, England. Participants: 23 773 CVI certifications issued from 2008 to 2009. Main Outcome measures: Crude and Age standardised rates of CVI data for blindness and sight loss by PCT. Methods: The crude and age standardised CVI rates per 100 000 were calculated with Spearman's rank correlation used to assess whether there was any evidence of association between CVI rates with Index of Multiple Deprivation (IMD) and the Programme Spend for Vision. Results: There was high-level variation, almost 11-fold (coefficient of variation 38%) in standardised CVI blindness and sight impairment annual certification rates across PCTs. The mean rate was 43.7 and the SD 16.7. We found little evidence of an association between the rate of blindness and sight impairment with either the IMD or Programme Spend on Vision. Conclusions: The wide geographical variation we found raises questions about the quality of the data and whether there is genuine unmet need for prevention of sight loss. It is a concern for public health practitioners who will be interpreting these data locally and nationally as the CVI data will form the basis of the public health indicator 'preventable sight loss'. Poor-quality data and inadequate interpretation will only create confusion if not addressed adequately from the outset. There is an urgent need to address the shortcomings of the current data collection system and to educate all public health practitioners.